SOCIOLINGUISTIC TENDENCIES OF THE ABBREVIATION WORD FORMATION OF NEW CREATIONS - NAMES OF PERSONS ACCORDING TO THE TYPE OF THEIR ACTIVITY IN THE FIRST DECADES OF THE XXI CENTURY - Voronina, Olha (Linguistic Bulletin (Movoznavchyi Visnyk), 2024)
Introduction. In last decades, there has been an expansion of nomination groups in the Ukrainian language. The lexical composition of the language is enriched by borrowings and derivatives forms from previously unproductive derivational bases. It takes place by the increased communicative function of the Ukrainian language in all spheres of social life following independence in 1991. The purpose is to investigate the grammatical innovations, the derivational basis of which includes both active abbreviations and lexical abbreviation neologisms resulting from the recent appearance of structures or phenomena. The aim is to identify the systematic nature of abbreviated nominative derivatives formation from the base of well-known active abbreviations. Also, we need to single out etalon forms of derived words from the such bases: ‘ZNO’, ‘MNS’, ‘IT’, ‘ATO’, ‘DSNS’, ‘OOS’, ‘TrO’. The methods. The main features of the linguistic analysis are implication of sources for the study of lexemes, analysis of the language system and verification based on intuition and observations of the researcher. For this exploration we made up a questionnaire in which respondents wrote possible abbreviated derivatives in their opinion. Main results of the study. There are invariant, or basic, and facultative manifestations in the creation of word-formation models of abbreviated derivatives. It was proved that the abbreviation as a root morpheme should be written according to pronunciation and on a par with other morphemes. That is why it is concluded that the root morpheme ‘zeeno-’ will be appropriate for an abbreviated nouns formed from the base of ‘ZNO’. Also, both the suffixes ‘-nyk’ and ‘-ets’ are the main productive for the creation of nominative derivatives-names of persons. The main interfixes are ‘iv’ and ‘ov’ which were used in the derivatives of respondents: ‘zeenovets’, ‘aitivets’, ‘atovets’ (with a morphemic suture at the boundary of the root and interfix), ‘oosivets’. Originality. The researching of grammatical innovations made possible to identify such standard abbreviated derivatives according to word-formation norms: ‘zeen/ov/ets’, ‘emenes/nyk’, ‘ait/iv/ets’, ‘at/ov/ets’, ‘deesenesh/nyk’, ‘oos/iv/ets’, ‘teer/ ov/ets’. These abbreviated derivatives are only examples among more lexemes like this. Native speakers had begun to produce them only in last decades. We can make sure of this after researching dictionaries. In the “Great Orthographic Dictionary of Modern Ukrainian Language”, published in 2008, provides only 7 nominative abbreviated derivatives out of 150,000 words: ‘bamivets’, ‘vuzivets’, ‘emteesivets’, ‘esesivets’, ‘ounivets’, ‘raykomivets’, ‘natovets’. In the dictionary "Word Formation of Independent Ukraine", published in 2017, number abbreviated nouns with suffixes ‘- ets’ (for example, ‘dukivets’ (from ‘DUK’), ‘fsbivets’, ‘idilevets’, etc.) and ‘-nyk’ (for example, ‘nabushnyk’, ‘bepepeshnyk’, ‘bibisishnyk’, ‘gpushnyk’) is already greater. That is why analysis abbreviated derivatives is originally and actually theme. Conclusions and specific suggestions of the author. The suffix method of word-formation is the main one in the creation of neologisms. The structure of abbreviated derivatives is predominantly as follows: root morpheme according to the phonetic properties of the abbreviation and written at the level with other formants, in lowercase, morphemic suture at the boundary with the interfix, suffix, ending. So, the rapid dynamic of abbreviated derivatives in the Ukrainian language is too noticeable. It requires further researches, particularly sociolinguistic.